Programmable proximity aperture lithography with MeV ion beams - Puttaraksa N. (2014)
A novel MeV ion beam programmable proximity aperture lithography system has been constructed at the Accelerator Laboratory of the University of Jyväskylä, Finland. This facility can be used to fabricate three dimensional microstructures in thick (<100 μm) polymer resist such as polymethylmethacrylate. In this method, MeV ion beams from the 1.7 MV pelletron and K130 cyclotron accelerators are collimated to a beam spot of rectangular shape. This shape is defined by a computer-controlled aperture made of a pair of L-shaped Ta blades which are in close proximity to the sample to minimize the penumbra broadening. Here the authors report on development of the system, the controlling software, the calibration procedures, investigations of multiple scattering effects, and present illustrative results using 3 MeV He 2+ 4 ion beams for lithography and 56 MeV N 3+ 14 ion beams for creating patterns of regions with ion tracks. © 2008 American Vacuum Society.